Physical development of hockey players aged 13-16 years - Surina-Marysheva, E. F.; Erlikh, V. V.; Korableva, Y. B.; Kantyukov, S. A.; Ermolaeva, E. N. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2018)
Aim. Identify the age features of hockey players aged 13-16 years old physical development. Material and methods. Elite hockey players (n = 83, age - 13-16 years) were surveyed. Standard anthropometric methods for measuring length and body weight were used. The body mass index (BMI) was calculated. Results. The average value of the body length of hockey players did not differ from peers, who do not engage in sports. The cental distribution of the absolute values of the indicator relative to nomograms has been shifted to the right. Most hockey players had average body lengths. The excess of the average body weight of hockey players was recorded in comparison with the average population values. The cental distribution of absolute values was characterized by a significant shift to the right (range 3% -90% percentile). Most hockey players had a body weight "above average" (55-66%). The group of athletes with body weight and BMI "below average" was 6% (age from 13 to 15 years). Conclusions. The physical development of elite hockey players is characterized by an average body length with a tendency to shift to values *above average*. The proportion of hockey players with mean body lengths below the mid-population is very small. Elite hockey players are characterized by large body weight and BMI compared to peers who do not engage in sports. As the age increases from the morphological criteria, the body weight and BMI have the greatest value for the hockey player`s success in sports selection.